I need help in this question please help.me ☺☺☺☺
Attachments:
![](https://hi-static.z-dn.net/files/da8/206a8df82f69184f0796eaa501ea3431.jpg)
Answers
Answered by
4
Heya☺
When roots are equal
D= 0
b^2-4ac=0
1. k^2-4×2×3=0
k^2- 24=0
k^2=24
k =√24
2.kx^2 - 2kx +6
(-2k)^2 - 4×k ×6=0
4k^2-24k = 0
4k^2 =24k
k^2=6k
k=6
✌✌
When roots are equal
D= 0
b^2-4ac=0
1. k^2-4×2×3=0
k^2- 24=0
k^2=24
k =√24
2.kx^2 - 2kx +6
(-2k)^2 - 4×k ×6=0
4k^2-24k = 0
4k^2 =24k
k^2=6k
k=6
✌✌
nitthesh7:
correct answer ☺☺☺☺
Similar questions